2015
DOI: 10.1681/asn.2015070815
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Mineralocorticoid Effects Determine Distal Salt Transport

Abstract: Excess aldosterone is an important contributor to hypertension and cardiovascular disease. Conversely, low circulating aldosterone causes salt wasting and hypotension. Aldosterone activates mineralocorticoid receptors (MRs) to increase epithelial sodium channel (ENaC) activity. However, aldosterone may also stimulate the thiazide-sensitive Na + -Cl 2 cotransporter (NCC). Here, we generated mice in which MRs could be deleted along the nephron to test this hypothesis. These kidney-specific MR-knockout mice exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
113
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 46 publications
13
113
0
1
Order By: Relevance
“…Interestingly, we also observed that the two days of dietary sodium restriction lowered plasma K + levels in mice. Consistent with a dominant role of plasma K + , two groups were just able to show that the down-regulation of NCC in mice with kidney-specific MR deletion could be overcome or at least mitigated by employing dietary K + restriction to normalize plasma K + [6,28]. Likewise, recent studies using mice deficient for 11βHSD2 by Hunter and colleagues challenged the conventional concept of mineralocorticoid signaling in the DCT [10].…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, we also observed that the two days of dietary sodium restriction lowered plasma K + levels in mice. Consistent with a dominant role of plasma K + , two groups were just able to show that the down-regulation of NCC in mice with kidney-specific MR deletion could be overcome or at least mitigated by employing dietary K + restriction to normalize plasma K + [6,28]. Likewise, recent studies using mice deficient for 11βHSD2 by Hunter and colleagues challenged the conventional concept of mineralocorticoid signaling in the DCT [10].…”
Section: Discussionmentioning
confidence: 92%
“…In the kidney, the disease familial hyperkalemic hypertension (FHHt) exemplifies how studying such genes can lead to the elucidation of novel regulatory pathways. The discovery that mutations in the With-no-lysine [K] kinases (WNKs) Wnk1 and Wnk4 cause FHHt (1,2) and, more recently, that mutations in Cullin 3 (Cul3) (OMIM 614496, PHA2E) (3)(4)(5) and Kelch-like 3 (Klhl3) (4, 5) -components of an E3 ubiquitin ligase complex -also cause the disease has revealed a canonical pathway for the regulation of the Na + Cl -cotransporter (NCC). Along the distal convoluted tubule (DCT), NCC is activated by phosphorylation at several amino-terminal residues (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…However, aldosterone administration increases urinary K ϩ loss, which, in turn, will reduce serum K ϩ levels and, thus, stimulate NCC activity. A recent study in mice in which the mineralocorticoid receptor was eliminated exclusively along the entire nephron strongly suggested that the aldosterone modulation of NCC is an indirect, rather than, direct effect of the changes in serum K ϩ (133). Furthermore, 11␤-hydroxysteroid dehydrogenase type 2 is not present in DCT1, and it is not clear whether it is expressed in DCT2 cells (reviewed in Ref.…”
Section: F137 Slc12 Cotransporters In the Kidneymentioning
confidence: 99%